1991
DOI: 10.1093/jmedent/28.2.266
|View full text |Cite
|
Sign up to set email alerts
|

New Procedures to Enhance Survival of Third-Instar Hypoderma lineatum (Villers) (Diptera: Oestridae) in Artificial Media

Abstract: New techniques for the maturation of late third instars of the common cattle grub, Hypoderma lineatum (Villers), in artificial media are described. Larvae were held in either 24-well culture plates with media plus penicillin, streptomycin sulfate, nystatin, and chloramphenicol or in small salve jars on Perlite and media plus the same antibiotics. Chloramphenicol was not always necessary in the jars. Survival to pupariation of young third instars increased from 5% without nystatin and chloramphenicol to 73% whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Wood (1987) points to the fact that immature oestrid larvae removed from their hosts invariably die rather than produce undersized adults, which strongly contrasts to species of Calliphoridae and Sarcophagidae parasitising or preying upon vertebrates. This may relate to derived physiological features shared by all Oestridae, as indicated by Chamberlain & Scholl (1991), who documented an extremely high susceptibility to bacteria in the non‐host environment for Hypoderma lineatum (Villers).…”
Section: Introductionmentioning
confidence: 99%
“…Wood (1987) points to the fact that immature oestrid larvae removed from their hosts invariably die rather than produce undersized adults, which strongly contrasts to species of Calliphoridae and Sarcophagidae parasitising or preying upon vertebrates. This may relate to derived physiological features shared by all Oestridae, as indicated by Chamberlain & Scholl (1991), who documented an extremely high susceptibility to bacteria in the non‐host environment for Hypoderma lineatum (Villers).…”
Section: Introductionmentioning
confidence: 99%
“…Daha önceki çalışmalarda antibiyotikler böceklerin yetiştirilmesini sağlayan yapay besin ortamına ilave edilerek mikrobiyal kontaminasyonları önlemek ve larvaların besin alımını uyarmak amacıyla kullanılmıştır (Pearson & Raybould, 1998;Büyükgüzel, 2001a;Büyükgüzel & Yazgan, 2002;Alverson & Cohen, 2002;Inglis & Cohen, 2004). Yapılan bu çalışmalar doğrultusunda kullanılan antibiyotiklerin düşük konsantrasyonlarının gelişimi hızlandırdığı, yaşama oranını, ergin ömür uzunluğunu ve vücut ağırlığını arttırdığı, yüksek konsantrasyonların ise böcekler üzerinde olumsuz etkileri olduğu ortaya çıkarılmıştır (Chamberlain & Schol, 1991;Hirose et al, 2006). Ancak, bu antibiyotiklerin böceğin yaşama oranı, gelişme süresi ve diğer biyolojik özelliklerini etkileyecek düzeyde oksidatif strese sebep olup olmadığı ve bu strese karşı antioksidatif tepki mekanizmasının uyarıldığı konusunda sınırlı sayıda çalışma bulunmaktadır (Büyükgüzel & Kalender, 2007;Büyükgüzel, 2009).…”
Section: Introductionunclassified
“…There have been no studies to investigate the positive effects of antimicrobial agents alone on parasitoid hymenopterous insects. However, one study with a parasitoid dipterous species Hypoderma lineatum (Villers) showed that a low level of chloramphenicol in the artificial diet significantly increased pupation by approximately 70.0% (C HAMBERLAIN and S CHOLL , 1991). It was demonstrated that novobiocin sodium, at the lowest tested level, caused a slight increase in the pupal and adult yields of another parasitoid dipterous insect, Agria affinis auct.…”
Section: Discussionmentioning
confidence: 99%